(untitled) - Huỳnh, Trung Tín (Cần Thơ, 2000)
This theorry includes many lessons: the nature of meaning, linguistic meaning, referential meaning, the dynamic dimension in communication, equivalence at word level, types of correspondences and contrasts, techniques of adjustment.
Keywords: English language,English language,Ngôn ngữ tiếng Anh,Ngôn ngữ tiếng Anh; Study and teaching,Translating,Phiên dịch,Dạy và học